Analisis Minat Mahasiswa FEB UB Menggunakan E-Money Brizzi: Model Kombinasi Technology Acceptance Model (TAM) And Theory of Planned Behavior (TPB) - Peggywati, Velenza Riyanda; Sakti, Rachmad Kresna (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to examine the factors which affect the intention to use e-money Brizzi. The factors which influenced student’s intention to use e-money Brizzi in the research are perceived usefulness, perceived ease of use, attitude, subjective norm and perceived behavior control. The combination model of TAM (Technology Acceptance Model) and TPB (Theory of Planned Behavior) is also used in this research. The research was done in Faculty of Economics and Business Brawijaya university trough the survey method. The researcher gained responds of 287students of 2011 Faculty of Economics and Business who are using the e-money Brizzi. Furthermore, the analysis was done by using the Software Smart PLS version 2.0 M3. The result of the research shows that construct of perceived usefulness, perceived ease of use, attitude, subjective norm and perceived behavior control influenced the student’s intention for using e-money Brizzi. Keywords: Electronic Money, BRIZZI, Perceived Usefulness, Perceived Ease of Use, Attitude, Subjective Norm, Perceived Behavioral Control, TAM and TPB.